Mechanism of Silver Sulfadiazine Action on Burn Wound Infections - Fox, Charles L. (1974)
The role of silver and sulfadiazine in the mechanism of action of silver sulfadiazine on burn wound infections was investigated. Silver, but not sulfadiazine, was bound by bacteria. Sulfadiazine did not act as an antibacterial agent in low concentrations, but exhibited specific synergism in combination with subinhibitory levels of silver sulfadiazine. The efficacy of silver sulfadiazine is thought to result from its slow and steady reactions with serum and other sodium chloride-containing body fluids, which permits the slow and sustained delivery of silver ions into the wound environs. In this circumstance, a relatively minute amount of sulfadiazine appears active.